A presença da Educação Estatística nos currículos dos cursos de formação inicial do professor que ensina Matemática - Gois Jr, Wanderley de Souza (2023)
The field of Statistical Education is increasingly gaining prominence, both on an international and national level, regardless of the context or country it is inserted in, becoming a topic of growing importance. Furthermore, its presence in the educational scenario of both Basic and Higher Education is of utmost relevance. As a result, national curriculum documents that guide Basic Education are starting to reflect the significant impact of Probability and Statistics in the world. Therefore, the initial changes in curriculum inserts began with the National Curriculum Parameters, still in the 1990s, being present in the thematic axis of Information Treatment. In the current and recent scenario, Probability and Statistics have been strengthened with the National Common Curriculum Base, making them even more significant. This is due to a separation in the thematic axis in which they were previously included, becoming a mandatory thematic unit in the curriculum, further reinforcing their importance. However, a new concern arises, questioning the initial training of teachers who teach Mathematics. Are Mathematics teachers being trained to effectively teach Probability and Statistics content? How do the pedagogical projects of Mathematics Education programs encompass these subjects? Are Probability and Statistics adequately addressed in Mathematics program evaluations? Therefore, this study will investigate whether the Probability and Statistics thematic unit of the National Common Curriculum Base is in line with international documents such as the Guidelines for Assessment and Instruction in Statistics Education (GAISE) and EDU-SET. It will also analyze how Probability and Statistics are incorporated into the curricula of Mathematics teacher education programs in the state of Rio Grande do Norte (RN), as well as how the National Student Performance Exam addresses the issues in this field. The aim is to highlight the current state of development in the training of teachers who teach Probability and Statistics and whether they are adequately prepared. The research adopted a qualitative and quantitative approach, concluding that Statistical Education prepares students to understand and deal with data and information in various areas of knowledge, promoting the development of critical thinking and decision-making skills. However, a weakness was identified in the initial training of Mathematics teachers regarding probabilistic and statistical content. The analysis of the curricula of Mathematics Education programs in RN revealed that Probability and Statistics topics are not extensively covered and have limited hours of instruction. Furthermore, there is a lack of pedagogical content related to Statistics in the curricula, including knowledge about teaching practices and methodological procedures. In summary, it is necessary to revise the curricula of initial teacher education programs to include more in-depth and pedagogically appropriate content on Probability and Statistics. Additionally, it is essential to promote greater appreciation for Statistical Education and provide continuing education opportunities for practicing teachers. Only through these measures will it be possible to develop a solid and comprehensive statistical education, equipping teachers to promote statistical literacy among students.